Issues on Gender Equality in the Qur'an Based on Amina Wadud's Hermeneutical Approach - Muhammad Resky; Akmal Rizki Gunawan Hasibuan (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This research aims to describe findings in the Qur'an regarding the issue of gender equality. Nowadays, there is still a stereotype of justifying men as having a higher position in reminding women who have done wrong. Even not a few men have a patriarchal paradigm towards women. The paradigm certainly needs to be straightened out through analysis of studies of several interpretations of the Qur'an. Using Amina Wadud's hermeneutic review as an approach, it was found that the Qur'an indeed explains the position between men and women with no dichotomy. By (1) categorizing interpretations into traditional, reactive, and holistic approaches and (2) identifying which methods best fit the analysis; philological analysis is then applied to examine the language and syntax of the Qur'anic text and uncover the deeper meanings of certain words and phrases The Qur'an does not describe the existence of patriarchal, matriarchal, misogynist, and misandry ideologies. Furthermore, it is also explained that (1) women have the right to inheritance and dowry, (2) they have the same commandments in worship, (3) men and women have a primordial agreement of monotheism, (4) men and women have the same potential to achieve achievements, and (5) men and women have compatibility in piety. These findings indicate that men and women have harmony before God and that there is no dichotomy between men and women in carrying out their functions and roles on earth.